Seismic assessment of a historical masonry arch bridg - Özmen, A.; Sayın, E. (My University, 2018)
Historical masonry arch bridges which are important components of the transportation in many placesworldwide are invaluable part of architectural and cultural heritage. These bridges, which date back tohundreds of years, have frequently been damaged or ruined because of unexpected events such asearthquakes. In this study, earthquake behaviour of a historical masonry arch bridge which called Dutpınaris analysed using 2003 Bingöl earthquake acceleration records. The bridge is modelled with threedimensional finite element software. Dynamic response of the bridge is investigated. For this purpose,displacement of the nodal point located at the top of the bridge is achieved. Also, maximum and minimumprincipal stress and strains are obtained and potential locations of initial damages are evaluated.
Keywords: Mimarlık; İnşaat Mühendisliği; Meteoroloji ve Atmosferik Bilimler